Hypoxia Enhances Oxidative Stress in Neutrophils from ZZ Alpha-1 Antitrypsin Deficiency Patients - María Magallón; Silvia Castillo-Corullón; Lucía Bañuls; Daniel Pellicer; Teresa Romero; Carlos Martínez-Ferraro; María Mercedes Navarro-García; Alberto Herrejón; Cruz González; Francisco Dasí (MDPI AG, 2023)
Alpha-1 antitrypsin deficiency (AATD) is a neutrophilic inflammatory disorder that may result in local hypoxia, reactive oxygen and nitrogen species (ROS/RNS) production, and increased damage in adjacent tissues. This study aims to determine the impact of hypoxia on neutrophil oxidative stress profile in AATD patients. Neutrophils were isolated from AATD patients and control volunteers and exposed to hypoxia (1% O2 for 4 h), ROS/RNS, mitochondrial parameters, and non-enzymatic antioxidant defenses measured by flow cytometry. The expression of enzymatic antioxidant defenses was determined by qRT-PCR. Our results indicate that ZZ-AATD neutrophils produce higher amounts of hydrogen peroxide, peroxynitrite, and nitric oxide and decreased levels of the antioxidant enzymes catalase, superoxide dismutase, and glutathione reductase. Likewise, our results show a decrease in mitochondrial membrane potential, indicating that this organelle could be involved in the production of the reactive species observed. No decrease in glutathione and thiol levels were observed. The accumulation of substances with high oxidative capacity would explain the greater oxidative damage observed in proteins and lipids. In conclusion, our results indicate that, compared to MM control individuals, ZZ-AATD neutrophils show increased ROS/RNS production under hypoxic conditions opening a new rationale for using antioxidant therapies to treat the disease.